SISTEM INFORMASI VERIFIKASI KELENGKAPAN SURAT PERTANGGUNGJAWABAN DESA KUALA DUA (E-SPJ) SEBAGAI PERCEPATAN ADMINSTRASI - Gultom, Asido Gerrald Iglasias (Jurnal KIAFE, 2023)
The E-SPJ is an information system design in the form of a website that is designed with the aim of verifying the completeness of the SPJ and as a storage database for the SPJ activity records that have been implemented. The design of the E-SPJ information system can also be used to see the completeness of the SPJ and can classify completed and incomplete SPJs. The method used in the design of the E-SPJ information system is to use the system approach and development method. The system approach method uses DFD (Data Flow Diagram) and the system development method uses the Waterfall Model method. The results of the design of the E-SPJ information system are in the form of a proposed system design and general description (design of the E-SPJ website display). The design of the E-SPJ information system is expected to help increase the effectiveness and smooth administration of the system, as well as anticipate findings of incomplete SPJ that have been carried out by work units or village officials in the Desa Kuala Dua Government.